Karakteristik Pati dari Batang Sagu Kalimantan Barat pada Tahap Pertumbuhan yang Berbeda - Maherawati Maherawati; Retno Budi Lestari; Haryadi Haryadi (agriTECH, 2011)
Sago (Metroxylon sagu Rottb.) is a potentially starch source crop. However, in West Kalimantan the use of sago is still limited. There is lack information about sago starch characteristics in relation to growth stages of the palm. Therefore, this study was aimed to observe the characteristics of sago starch extracted from the trunk at variatious growth stages. Sago trunks were taken from Sui Bemban and Sui Ambawang villages, Kubu Raya regency, West Kalimantan. They were classified into four different physiological growth stages, namely dewasa (9 yr), jantung (10 yr), rusa (11 yr), and bunga (12 yr old). The starch was extracted in laboratory and then dried at 50 °C. Dried sago starches were analyzed for their chemical compositions (moisture, fat, protein, ash, carbohydrate, fibre, and amylose contents), physical cha- racteristics (colour and the granule form), functional characteristics (water absorpsion, oil absorpsion, swelling power, and solubility). Pasting properties were  characterized by Brabender amylograhpy. Results indicated that chemical composition and physical characteristics of the sago starches extracted from 9-12 year-old trunks were not signifi- cantly differrent. The highest rendement obtained from 10 – 11 year-old trunks. Amylose content was 41.8 % which was categorized as high. Functional characteristics as shown by the amylograph revealed that sago starch has type-C curve. Starch extracted from 9 yr old trunk gave the highest paste viscosity which was the most suitable for for use in product that needs a strong gelling property.ABSTRAKSagu (Metroxylon sagu Rottb.) sangat potensial sebagai sumber pati, namun di Kalimantan Barat pemanfaatan sagu sebagai sumber pati masih terbatas. Belum ada informasi mengenai hubungan tahap pertumbuhan dengan sifat-sifat pati sagu yang dihasilkan. Penelitian ini bertujuan untuk mengetahui karakteristik pati sagu pada beberapa tahap pertumbuhan. Tanaman sagu diperoleh dari Desa Sui Bemban dan Sui Ambawang Kecamatan Kubu Kabupaten Kubu Raya Kali- mantan Barat. Tanaman dikelompokkan menjadi empat fase yaitu dewasa (9 tahun), jantung (10 tahun), rusa (11 tahun), dan bunga (12 tahun). Pati sagu diekstrak di laboratorium kemudian dikeringkan pada suhu 50 °C. Pati kering dianalisa komposisi kimia (kadar air, lemak, protein, kadar abu, karbohidrat, serat kasar, dan amilosa), sifat fisik (warna dan ben- tuk granula), sifat fungsional (daya serap air, daya serap minyak, swelling power, dan solubility). Sifat amilografi dinali- sis dengan Brabender amylograhpy. Hasil penelitian menunjukkan bahwa sifat kimia dan fisik pati sagu yang diekstrak dari batang sagu umur 9-12 tahun tidak berbeda nyata. Batang sagu berumur 10-11 tahun memberi rendemen tertinggi. Kadar amilosa mencapai 41,8 %. Kurva amilografi menunjukkan bahwa pati sagu mempunyai kurva amilogram tipe-C. Pati dari batang berumur 9 tahun menunjukkan ciri viskositas yang tinggi dan yang sangat sesuai untuk